Capital Market Development and Labor Absorption in the Financial Sector: A Systematic Literature Review - Rita Rita; Dhenok Darwanti; Evi Okli Lailani; Siti Maryam; Patria Adiguna (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study examines the relationship between capital market development and labor absorption in the financial sector through a systematic literature review approach. The originality of this research lies in its specific focus on the sectoral employment impact of capital market development within the financial industry, an area that has received limited comprehensive synthesis in prior studies. The objective of this study is to identify the patterns of relationship, transmission mechanisms, and structural changes associated with capital market expansion and employment dynamics in the financial sector. The research method applies a systematic literature review by analyzing peer-reviewed journal articles indexed nationally and internationally within the period 2000–2024. The empirical findings indicate that capital market development generally contributes positively to labor absorption through the expansion of financial institutions, increased trading activities, and financial product innovation. However, technological advancement, digitalization, and automation significantly reshape labor demand toward technology-based and analytical competencies. The implications of this study emphasize the importance of aligning capital market development policies with human capital enhancement strategies to ensure inclusive and sustainable job creation in the financial sector